The results and methodological concerns about pharmaco-economic evaluation in anesthesia - Majstorović Branislava M.; Milaković Branko D.; Marković Srđan Z.; Mijajlović Miloš S.; Kastratović Dragana A. (Hospital Pharmacology, 2014)
Background Globalization and profitable health (cost/benefit) requires pharmacoeconomic evaluation of the costs in relation to effectiveness of the methods of treatment. The objective of this study was to analyze the cumulative costs of anesthesia in all surgical disciplines using the Activity-Based Costing (ABC) analysis. Methods This work is a part of Phase IV clinical study. Retrospectively, for 2006, direct costs of anesthesia services were calculated: (1) personnel costs (salaries), (2) drugs and supplies, (3) other costs (analysis and apparatus) in the Institute of Anesthesiology and Resuscitation, Clinical Center of Serbia. The research group included all anesthetized patients of both genders and ofall ages. Summary data documented in the anesthesia department and databases of the Clinical Center of Serbia and the Republic Institute of Health Insurance were used. Numerical data were calculated and analyzed by computer programs Microsoft Office Excel 2003 and SPSS for Windows. Results The results of direct costs showed that personnel costs accounted for 40%, medicines and supplies - 31.80% and other costs - 28.20% of the funds. Anesthesia costs accounted for 10% (ABC analysis) of direct costs. Methodological dilemmas were related to the inaccuracy of anesthetic and surgical protocols, the classification of anesthetic and surgical services and the imperfection of computer data entry software. Basic hospital activities information should be more specific and precise. Clinical protocols of the anesthetized patients should be connected better with the Admission department, Intensive care units, Day surgical hospital and other departments. Database of the clinical drug pathway, Clinical protocols, Accounting Information Systems, and Hospital Management Information Systems should be precise, specific and managed in a better way. Conclusions The costs of local and general anesthesia procedures are objectively low and numerous, what may be objectified by this pharmacoeconomic analysis. Those insufficiently informed call for 'rationalization'. The costs of drugs and supplies are real while all other costs are agreed upon, and accordingly, there is no possibility of cutting down the expenses within so small and restrictive health budget. The change of budget dynamics and education of control staff could be helpful.